Efficient stable multifunctional catalyst and preparation method thereof
By using carbon fiber composite carbon nanotubes to support Fe-Co, Fe-Ni or Co-Ni nanoparticles, metal nitrides and metal phosphides in oxygen electrocatalysts, poor stability and insufficient versatility of existing oxygen electrocatalysts are solved. The problem is to achieve efficient and stable multifunctional catalytic effect.
Patent Information
- Application Number
- CN202411591295.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-14
AI Technical Summary
The poor stability and lack of versatility of existing oxygen electrocatalysts limit their application in clean and sustainable energy installations.
Using carbon-based supported bimetallic nanoparticle catalyst, the carbon-based carbon fiber composite carbon nanotubes are supported by Fe-Co, Fe-Ni or Co-Ni nanoparticles, metal nitrides and metal phosphides, and through electrospinning and vapor deposition Technical preparation.
The conductivity and active site utilization efficiency of the catalyst are improved, the activities of oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) are enhanced, and efficient and stable multifunctional catalytic effect is achieved.
Smart Images

Figure BDA0005125655830000101 
Figure BDA0005125655830000102 
Figure BDA0005125655830000111
Abstract
Description
Technical Field
[0001] The present application relates to the field of oxygen electrocatalysts, and in particular to a highly efficient, stable and multifunctional catalyst and a preparation method thereof. Background Art
[0002] Nowadays, energy shortage and climate change have triggered an urgent need to accelerate the commercialization of clean energy. Among them, developing excellent energy storage and conversion systems is one of the keys to studying renewable clean energy. Fuel cells and metal-air batteries have attracted widespread attention in the energy field due to their high specific energy and stability. However, both energy sources require efficient oxygen electrocatalysts.
[0003] Currently, the most effective OER (oxygen evolution reaction) and ORR (oxygen reduction reaction) electrocatalysts are Ir / Ru and Pt-based materials, respectively. However, the high cost, low abundance and poor stability of these noble metal materials hinder their commercial application. In addition, the lack of multifunctionality is also a clear disadvantage for the development of these electrocatalysts in clean and sustainable energy devices. Summary of the invention
[0004] In order to solve the problems of poor stability and lack of multifunctionality of current oxygen electrocatalysts, the present application provides a highly efficient, stable and multifunctional catalyst and a preparation method thereof.
[0005] In the first aspect, the present application proposes a highly efficient, stable and multifunctional catalyst, wherein the multifunctional catalyst is a carbon-based loaded bimetallic nanoparticle catalyst; the carbon-based catalyst is a carbon fiber composite carbon nanotube; the bimetallic nanoparticle is one of Fe-Co nanoparticles, Fe-Ni nanoparticles and Co-Ni nanoparticles; the carbon-based catalyst is also loaded with metal nitrides and metal phosphides.
[0006] Preferably, the metal nitride is Fe-N x Coordination compounds, Co-N x Coordination compounds and Ni-N x At least one of the coordination compounds; the metal phosphide is Fe-P x Coordination compounds, Co-P x Coordination compounds and Ni-P x At least one of the coordination compounds.
[0007] By adopting the above technical scheme, on the first hand, the multifunctional catalyst provided in the present application uses a carbon base as a carrier material, specifically, the carbon base is a carbon fiber composite carbon nanotube. Compared with general carbon-based materials, there are problems such as simple structure and low porosity, which leads to limited exposure of active sites of the catalyst. The carbon fiber composite carbon nanotube has a high degree of porosity, and the fiber network as a carbon substrate has a high porosity and a large specific surface area. The composite carbon nanotubes are staggered on the surface of the carbon fiber, and together with the fiber network, promote mass transfer in the electrocatalytic process, improve the conductivity of the catalyst, and thus accelerate the catalytic process. In addition, there is a certain spacing effect in the carbon fiber, and a large number of active sites are exposed on the defect-rich porous carbon base, making it easier for the active sites to contact with oxygen, electrolytes and electrons, thereby improving the utilization efficiency of the active sites and thus improving the catalytic activity of the catalyst.
[0008] On the second aspect, bimetallic nanoparticles are loaded on the carbon base. Specifically, the bimetallic nanoparticles include one of Fe-Co nanoparticles, Fe-Ni nanoparticles and Co-Ni nanoparticles. Different combinations of bimetallic nanoparticles can be selected according to actual needs during use to achieve higher catalytic effects. Compared with single metal nanoparticles, alloy particles of two metals are more likely to form MOOH / MOH bonds on their surfaces, where M represents metal atoms, and MOOH / MOH plays a leading role in OER. Bimetallic nanoparticles can significantly improve the reaction activity of OER. In addition, the interaction between the two different metals can improve the ORR activity, and the mutual combination between carbon nanotubes and transition metals can improve the conductivity and dispersibility of electrons and improve the ORR activity. The introduction of bimetallic nanoparticles can improve the ORR / OER activity, so that the obtained catalyst has a dual catalytic effect.
[0009] On the third aspect, the carbon base of the catalyst of the present application is also loaded with metal nitrides and metal phosphides. Specifically, the metal nitrides and metal phosphides are metal nitrogen coordination compounds and metal phosphorus coordination compounds, respectively. The metal heteroatom bonds contained in the metal nitrogen coordination compounds can reduce the binding energy of intermediates in ORR and improve the reaction activity of ORR, while the metal phosphorus coordination compounds are effective active substances for ORR / OER. The addition of metal nitrides and metal phosphides can help form more efficient multifunctional catalysts.
[0010] Preferably, the carbon fiber composite carbon nanotube contains nitrogen-doped graphene.
[0011] By adopting the above technical solution, in the preparation process of the multifunctional catalyst of the present application, nitrogen-doped graphene will be formed on the carbon base. On the one hand, the defects contained in the multilayer graphene formed on the surface can provide a place for constructing active substances, and can also cover the metal active substances formed in the preparation process, thereby increasing the stability of the catalyst; on the other hand, the graphene is also doped with nitrogen, which can improve the conductivity of the carbon base, promote the electron transfer inside the catalyst, reduce the interface resistance, and thus improve the catalytic activity of the catalyst. More metal nitrides and metal phosphides can be formed on the matrix of nitrogen-doped graphene, which can also improve the activity of bimetallic nanoparticles and the stability of the encapsulation, and improve the OER / ORR activity.
[0012] Preferably, the carbon fiber composite carbon nanotube further contains dihydroxy cage silsesquioxane; the raw materials of the dihydroxy cage silsesquioxane include octavinyl cage silsesquioxane monomer and 2-mercaptoethanol in a mass ratio of 1:(0.35-0.4).
[0013] Preferably, the preparation method of dihydroxy cage silsesquioxane is as follows: Octavidin cage silsesquioxane and 2-mercaptoethanol are mixed and added to a solvent, and then a photoinitiator is added, stirred and dispersed for 10 to 20 minutes, and then stirred and reacted for 50 to 60 minutes under ultraviolet light. After the reaction is completed, chromatographic separation, recrystallization, and vacuum drying are performed to obtain dihydroxy cage silsesquioxane.
[0014] Preferably, the solvent is tetrahydrofuran.
[0015] Preferably, the photoinitiator is 2,2-dimethylol propionic acid, and the amount of the photoinitiator added is 1.5-2% of the mass of the octavinyl cage silsesquioxane.
[0016] By adopting the above technical solution, active hydroxyl groups are linked at the two vertices of the dihydroxy cage silsesquioxane, which can improve the compatibility of the dihydroxy cage silsesquioxane in the spinning polymer and improve the dispersibility of metal ions in the spinning precursor solution, so that the bimetallic nanoparticles in the formed catalyst can be evenly dispersed.
[0017] Secondly, the special cage structure and hydroxyl active sites of dihydroxy cage silsesquioxane can also load metal ions, improve the catalytic activity of carbon-based loaded bimetallic nanoparticle catalysts, and the porous channels in its molecules are also conducive to the conduction of metal ions. Combining with the carbon base of the multifunctional catalyst of the present application can promote mass transfer in the electrocatalytic process, improve the conductivity of the catalyst, and further obtain an efficient multifunctional catalyst. In addition, the bond energy of the silicon-oxygen bond contained in the molecular structure of dihydroxy cage silsesquioxane is higher than the bond energy of the carbon-carbon bond, the inorganic silicon-oxygen rigid skeleton contained can improve the stability of the carbon base, and the hydroxyl group contained can improve the binding force in the carbon fiber composite carbon nanotube, further improving the stability of the multifunctional catalyst.
[0018] Finally, the dihydroxy cage silsesquioxane has a nanometer size. During the preparation of the multifunctional catalyst, its dihydroxy cage silsesquioxane molecules can absorb the energy generated in the system and reduce the stress concentration problem existing in the carbon base, thereby improving the stability of the obtained multifunctional catalyst.
[0019] In a second aspect, the present application also provides a method for preparing a highly efficient and stable multifunctional catalyst, comprising the following steps: S1. adding a metal salt to a solvent, stirring and dissolving the metal salt, and then adding the metal salt to a spinning precursor solution, stirring and dispersing the solution to obtain a spinning precursor solution containing metal ions; and then electrospinning to obtain a composite fiber containing bimetallic nanoparticles; S2. The composite fiber obtained in step S1 is first dried and then heat treated under an ammonia gas flow to obtain a carbon fiber composite carbon nanotube loaded with bimetallic nanoparticles; S3. The obtained carbon fiber composite carbon nanotubes loaded with bimetallic nanoparticles and the nitrogen precursor are placed in the same crucible and vapor deposited in a nitrogen atmosphere; after the reaction is completed, the product and the phosphorus precursor are placed in two different crucibles and vapor deposited in a nitrogen atmosphere, and a highly efficient, stable and multifunctional catalyst is obtained after cooling.
[0020] Preferably, the solvent is N,N-dimethylformamide.
[0021] Preferably, in step S3, during the vapor deposition of carbon fiber composite carbon nanotubes loaded with bimetallic nanoparticles and a nitrogen precursor, the reaction temperature is 950-1000°C, and the reaction time is 1-1.5 h; during the vapor deposition of a product obtained after the reaction of carbon fiber composite carbon nanotubes loaded with bimetallic nanoparticles and a nitrogen precursor and a phosphorus precursor, the reaction temperature is 400-450°C, and the reaction time is 2-2.5 h.
[0022] By adopting the above technical scheme, the present application first obtains composite fibers through electrospinning, which can make the formed carbon-based carrier have higher porosity and larger specific surface area. In this process, metal ions are introduced into the spinning precursor solution through metal salts, which is beneficial to the uniform dispersion of metal ions in the composite fibers. Then, carbon fiber composite carbon nanotubes loaded with bimetallic nanoparticles are obtained through heat treatment, so that the bimetallic nanoparticles can be evenly transferred on the carbon fiber composited with carbon nanotubes. Finally, a multifunctional catalyst is obtained through vapor deposition technology, and metal nitrides and metal phosphides are formed on the carbon fiber composite carbon nanotubes loaded with bimetallic nanoparticles, thereby improving the ORR / OER activity and further increasing the catalytic activity of the catalyst.
[0023] Preferably, in the step S1, a 19-gauge needle is used for electrospinning, and the spinning speed is 0.5 to 1 ml / h; during the electrospinning process, positive and negative voltages need to be loaded simultaneously, the positive voltage is 15 to 20 kv, and the negative voltage is -0.2 to 0.8 kv.
[0024] Preferably, the relative humidity of the air during the electrospinning process is 15-40%, and the temperature is 18-30°C.
[0025] By adopting the above technical solution, in order to obtain dimensionally stable composite fibers during the electrospinning process, a No. 19 needle is selected for spinning. A needle that is too thin may cause the spinning precursor to be unable to be sprayed evenly and stably, and it is difficult to migrate to the substrate under the action of the magnetic field force, while a needle that is too thick may cause the spinning precursor to be unable to form a spray state and flow out directly in the form of droplets, and thus unable to form a fibrous substance. In addition, positive and negative voltages need to be loaded simultaneously during the electrospinning process, which is conducive to the formation of a nanofiber network.
[0026] Preferably, in step S2, the heat treatment temperature is 750-800° C., and the heat treatment time is 2-2.5 h.
[0027] By adopting the above technical scheme, the heat treatment is carried out under the flow of ammonia gas. Under high temperature conditions, the graphitization of the composite fiber gradually increases, and under the flow of ammonia gas, nitrogen-doped graphene is gradually formed, and the overall nanofiber network gradually forms a carbon fiber structure, and carbon nanotubes are also compounded on the surface of the carbon fiber, so that the obtained carbon base has porosity and high specific surface area, which promotes the mass transfer of the electrocatalyst, and the bimetallic nanoparticles can also be stably loaded on the carbon base.
[0028] Preferably, the metal salt includes a combination of at least two of ferric nitrate nonahydrate, cobalt nitrate hexahydrate, cobalt acetate hexahydrate, ferrous sulfate heptahydrate, nickel nitrate hexahydrate, and nickel sulfate hexahydrate; the mass ratio of the metal salt to the spinning precursor solution is (0.15-0.2):1.
[0029] By adopting the above technical solution, metal ions are introduced into the spinning precursor solution through metal salts, which can improve the dispersibility of metal ions on the carbon-based carrier and is also beneficial to the formation and loading of bimetallic nanoparticles.
[0030] Preferably, the spinning precursor solution comprises a spinning polymer and dihydroxy cage-type silica in a mass ratio of 1:(0.05-0.15); the spinning polymer comprises one or a combination of polyacrylonitrile, polyaniline, and polyvinyl pyrrolidone.
[0031] By adopting the above technical scheme, the spinning polymer contains nitrogen atoms, which is beneficial to the formation of nitrogen-doped graphene, which can further improve the conductivity of the catalyst. The addition of nitrogen-doped graphene is also beneficial to the loading of metal nanoparticles, which is beneficial to the construction of active sites, improves ORR / OER activity, and further improves the catalytic activity of the catalyst.
[0032] Preferably, the nitrogen precursor includes one or a combination of dicyandiamide, urea, and melamine; the phosphorus precursor includes one or a combination of diammonium phosphate, sodium hypophosphite, and diammonium hydrogen phosphate; the mass ratio of the carbon fiber composite carbon nanotube loaded with bimetallic nanoparticles to the nitrogen precursor is 1:(3.5~4.5); the mass ratio of the carbon fiber composite carbon nanotube loaded with bimetallic nanoparticles to the phosphorus precursor is 1:(3~4).
[0033] By adopting the above technical scheme, under high temperature conditions, nitrogen precursors and phosphorus precursors can be decomposed into nitrogen-containing vapor and phosphorus-containing vapor, which can further coordinate with the bimetallic nanoparticles loaded on some carbon fiber composite carbon nanotubes to obtain corresponding metal nitrogen compounds and late metal phosphorus compounds, further effectively improving the ORR / OER activity, thereby improving the catalytic activity of the catalyst.
[0034] In summary, this application has the following beneficial effects: 1. The multifunctional catalyst of the present application is a carbon-based supported bimetallic nanoparticle catalyst, wherein the carbon-based is a carbon fiber composite carbon nanotube, which has a high porosity and a large specific surface area, can promote mass transfer in the electrocatalytic process, improve the conductivity of the catalyst, thereby accelerating the catalytic process, and the carbon fiber composite carbon nanotube can expose a large number of active sites, making the active sites more easily contacted with oxygen, electrolytes and electrons, thereby improving the utilization efficiency of the active sites, and then improving the catalytic activity of the catalyst. The bimetallic nanoparticles can select different metal particle combinations according to actual needs, which can improve the ORR / OER activity, so that the obtained catalyst has a dual catalytic effect.
[0035] 2. In the multifunctional catalyst of the present application, metal nitrides and metal phosphides are also loaded on the carbon base. Specifically, metal nitrogen coordination compounds and metal phosphorus coordination compounds are effective active substances for ORR / OER, and their addition can help form a more efficient multifunctional catalyst.
[0036] 3. The multifunctional catalyst of the present application also contains dihydroxy cage-type silsesquioxane on the carbon base. The hydroxyl active sites contained in the dihydroxy cage-type silsesquioxane can also load metal ions, thereby improving the catalytic activity of the carbon-based loaded bimetallic nanoparticle catalyst. The porous channels in the molecules are also conducive to the conduction of metal ions. Combining with the carbon base of the multifunctional catalyst of the present application can promote mass transfer in the electrocatalytic process and improve the conductivity of the catalyst. In addition, the dihydroxy cage-type silsesquioxane can also absorb the energy generated in the system and reduce the stress concentration problem existing in the carbon base, thereby improving the stability of the obtained multifunctional catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a SEM scanning electron microscope image of the highly efficient, stable and multifunctional catalyst obtained in Example 1. DETAILED DESCRIPTION
[0038] Preparation Example of Bishydroxy Cage Silsesquioxane Preparation Example 1: A dihydroxy cage silsesquioxane is prepared according to the following method: 10 g of octavinyl cage silsesquioxane and 3.8 g of 2-mercaptoethanol were mixed and added to 100 ml of dried tetrahydrofuran, and then 0.18 g of 2,2-dihydroxymethylpropionic acid was added, stirred and dispersed for 15 minutes, and then stirred and reacted under ultraviolet light for 50 minutes. After the reaction, chromatographic separation, recrystallization and vacuum drying were performed to obtain dihydroxy cage silsesquioxane.
[0039] Preparation Example 2, a dihydroxy cage-type silsesquioxane, is different from Preparation Example 1 only in that the added amount of 2-mercaptoethanol is 3.5 g.
[0040] Preparation Example 3, a dihydroxy cage-type silsesquioxane, is different from Preparation Example 1 only in that the amount of 2-mercaptoethanol added is 4 g.
[0041] Preparation Example 4, a dihydroxy cage-type silsesquioxane, is different from Preparation Example 1 only in that the amount of 2-mercaptoethanol added is 3 g.
[0042] Preparation Example 5, a dihydroxy cage-type silsesquioxane, is different from Preparation Example 1 only in that the amount of 2-mercaptoethanol added is 4.5 g. Example
[0043] Example 1, a highly efficient and stable multifunctional catalyst, prepared according to the following method: S1. Add 1.8 g of metal salt (the metal salt is ferric nitrate nonahydrate and cobalt acetate hexahydrate in a mass ratio of 2:1) to 100 ml of N,N-dimethylformamide and stir to dissolve, then add to 10 g of spinning precursor solution and continue to stir and disperse to obtain a spinning precursor solution containing metal ions, wherein the spinning precursor solution is polyacrylonitrile and the dihydroxy cage-type silsesquioxane prepared in Preparation Example 1 in a mass ratio of 1:0.1.
[0044] Then, composite fibers containing bimetallic nanoparticles are obtained by electrospinning. During the electrospinning process, a No. 19 needle is used, the spinning speed is 0.8 ml / h, the relative humidity of the air is controlled at 30%, the temperature is 25°C, and positive and negative voltages are loaded at the same time, wherein the positive voltage is 18 kv and the negative voltage is 0.1 kv.
[0045] S2. The composite fiber obtained in step S1 is vacuum dried at 120°C for 6 hours, and then heat-treated under an ammonia gas flow, wherein the heat treatment heating rate is 2°C / min, heated to 800°C, and the heat treatment time is 2 hours to obtain a carbon fiber composite carbon nanotube loaded with bimetallic nanoparticles; S3. 10g of the obtained carbon fiber composite carbon nanotube loaded with bimetallic nanoparticles and 40g of dicyandiamide were placed in the same crucible and vapor deposited in a nitrogen atmosphere. During the vapor deposition process, they were first heated to 300°C at a heating rate of 5°C / min, and then heated to 1000°C at a heating rate of 2°C / min. The reaction time was 1h, and then the temperature was adjusted to 300°C at a cooling rate of 7°C / min, and finally naturally cooled to room temperature; then the product and 35g of sodium hypophosphite were placed in two different crucibles and vapor deposited in a nitrogen atmosphere. During the vapor deposition process, the temperature was increased to 400°C at a heating rate of 2°C / min, and then the temperature was maintained for 2h. Finally, it was naturally cooled to room temperature to obtain an efficient, stable and multifunctional catalyst.
[0046] Example 2, a highly efficient, stable and multifunctional catalyst, is different from Example 1 only in that in step S1, the amount of metal salt added is 1.5 g, and the metal salt is still ferric nitrate nonahydrate and cobalt acetate hexahydrate in a mass ratio of 2:1.
[0047] Example 3, a highly efficient, stable and multifunctional catalyst, is different from Example 1 only in that in step S1, the amount of metal salt added is 2 g, and the metal salt is still ferric nitrate nonahydrate and cobalt acetate hexahydrate in a mass ratio of 2:1.
[0048] Example 4, a highly efficient, stable and multifunctional catalyst, is different from Example 1 only in that in step S1, the spinning precursor solution is polyacrylonitrile and the dihydroxy cage-type silsesquioxane prepared in Preparation Example 1 in a mass ratio of 1:0.05.
[0049] Example 5, a highly efficient, stable and multifunctional catalyst, is different from Example 1 only in that in step S1, the spinning precursor solution is polyacrylonitrile and the dihydroxy cage-type silsesquioxane prepared in Preparation Example 1 in a mass ratio of 1:0.15.
[0050] Example 6, a highly efficient, stable and multifunctional catalyst, is different from Example 1 only in that the amount of dicyandiamide added in step S3 is 35 g.
[0051] Example 7, a highly efficient, stable and multifunctional catalyst, is different from Example 1 only in that the amount of dicyandiamide added in step S3 is 45 g.
[0052] Example 8, a highly efficient, stable and multifunctional catalyst, is different from Example 1 only in that the amount of sodium hypophosphite added in step S3 is 30 g.
[0053] Example 9, a highly efficient, stable and multifunctional catalyst, is different from Example 1 only in that the amount of sodium hypophosphite added in step S3 is 40 g.
[0054] Example 10, a highly efficient, stable and multifunctional catalyst, is different from Example 1 only in that, during the electrospinning process in step S1, the positive voltage is adjusted to 15 kV and the negative voltage is adjusted to 0.8 kV.
[0055] Example 11, a highly efficient, stable and multifunctional catalyst, is different from Example 1 only in that, during the electrospinning process in step S1, the positive voltage is adjusted to 20 kV and the negative voltage is adjusted to -0.2 kV.
[0056] Example 12, a highly efficient, stable and multifunctional catalyst, is different from Example 1 only in that the heating rate during the heat treatment in step S2 is 2°C / min, the temperature is heated to 750°C, and the heat treatment time is 2.5h.
[0057] Example 13, a highly efficient, stable and multifunctional catalyst, is different from Example 1 only in that an equal amount of the dihydroxy cage silsesquioxane prepared in Preparation Example 2 is used to replace the dihydroxy cage silsesquioxane prepared in Preparation Example 1.
[0058] Example 14 is a highly efficient, stable and multifunctional catalyst, which is different from Example 1 only in that the bishydroxy cage silsesquioxane prepared in Preparation Example 1 is replaced by an equal amount of the bishydroxy cage silsesquioxane prepared in Preparation Example 3.
[0059] Example 15, a highly efficient, stable and multifunctional catalyst, differs from Example 1 only in that the metal salt obtained by combining ferric nitrate nonahydrate and nickel nitrate hexahydrate in an equal mass ratio of 2:1 is used to replace the metal salt obtained by combining ferric nitrate nonahydrate and cobalt acetate hexahydrate in an equal mass ratio of 2:1.
[0060] Example 16, a highly efficient, stable and multifunctional catalyst, differs from Example 1 only in that the metal salt obtained by combining cobalt acetate hexahydrate and nickel nitrate hexahydrate in an equal mass ratio of 2:1 is used to replace the metal salt obtained by combining iron nitrate nonahydrate and cobalt acetate hexahydrate in a mass ratio of 2:1.
[0061] Example 17, a highly efficient, stable and multifunctional catalyst, differs from Example 1 only in that, in step S1, the amount of the metal salt added, which is obtained by combining ferric nitrate nonahydrate and cobalt acetate hexahydrate in a mass ratio of 2:1, is 1.2 g.
[0062] Example 18, a highly efficient, stable and multifunctional catalyst, differs from Example 1 only in that, in step S1, the amount of the metal salt added, which is obtained by combining ferric nitrate nonahydrate and cobalt acetate hexahydrate in a mass ratio of 2:1, is 2.2 g.
[0063] Example 19, a highly efficient, stable and multifunctional catalyst, is different from Example 1 only in that an equal amount of the dihydroxy cage silsesquioxane prepared in Preparation Example 4 is used to replace the dihydroxy cage silsesquioxane prepared in Preparation Example 1.
[0064] Example 20, a highly efficient, stable and multifunctional catalyst, is different from Example 1 only in that an equal amount of the dihydroxy cage silsesquioxane prepared in Preparation Example 5 is used to replace the dihydroxy cage silsesquioxane prepared in Preparation Example 1.
[0065] Example 21, a highly efficient, stable and multifunctional catalyst, is different from Example 1 only in that in step S1, the spinning precursor liquid is polyacrylonitrile and the dihydroxy cage-type silsesquioxane prepared in Preparation Example 1 in a mass ratio of 1:0.02.
[0066] Example 22, a highly efficient, stable and multifunctional catalyst, is different from Example 1 only in that in step S1, the spinning precursor liquid is polyacrylonitrile and the dihydroxy cage-type silsesquioxane prepared in Preparation Example 1 in a mass ratio of 1:0.2.
[0067] Example 23, a highly efficient, stable and multifunctional catalyst, differs from Example 1 only in that in step S1, an equal amount of polyacrylonitrile is used to replace the spinning precursor solution obtained by combining polyacrylonitrile and dihydroxy cage-type silsesquioxane prepared in Preparation Example 1 in a mass ratio of 1:0.15.
[0068] Example 24, a highly efficient, stable and multifunctional catalyst, is different from Example 1 only in that the amount of dicyandiamide added in step S3 is 30 g.
[0069] Example 25, a highly efficient, stable and multifunctional catalyst, is different from Example 1 only in that the amount of dicyandiamide added in step S3 is 50 g.
[0070] Example 26, a highly efficient, stable and multifunctional catalyst, is different from Example 1 only in that the amount of sodium hypophosphite added in step S3 is 25 g.
[0071] Example 27, a highly efficient, stable and multifunctional catalyst, is different from Example 1 only in that the amount of sodium hypophosphite added in step S3 is 45 g.
[0072] Example 28, a highly efficient, stable and multifunctional catalyst, is different from Example 1 only in that in step S1, a No. 18 needle is used during the electrospinning process.
[0073] Example 29, a highly efficient, stable and multifunctional catalyst, is different from Example 1 only in that a No. 20 needle is used during the electrospinning process in step S1.
[0074] Comparative Example Comparative Example 1, a highly efficient, stable and multifunctional catalyst, differs from Example 1 only in that, in step S1, an equal amount of ferric nitrate nonahydrate is used to replace the metal salt obtained by combining ferric nitrate nonahydrate and cobalt acetate hexahydrate in a mass ratio of 2:1.
[0075] Comparative Example 2, a highly efficient, stable and multifunctional catalyst, is different from Example 1 only in that, in step S3, 10 g of the obtained carbon fiber composite carbon nanotube loaded with bimetallic nanoparticles and 35 g of sodium hypophosphite are placed in two different crucibles, and vapor deposition is performed under a nitrogen atmosphere. During the vapor deposition process, the temperature is increased to 400°C at a heating rate of 2°C / min, and then the temperature is maintained for 2 hours, and finally naturally cooled to room temperature to obtain a highly efficient, stable and multifunctional catalyst. During this period, no vapor deposition is performed with dicyandiamide.
[0076] Comparative Example 3, a highly efficient, stable and multifunctional catalyst, differs from Example 1 only in that, in step S3, 10 g of the obtained carbon fiber composite carbon nanotube loaded with bimetallic nanoparticles and 40 g of dicyandiamide are placed in the same crucible and vapor deposited under a nitrogen atmosphere. During the vapor deposition process, it is first heated to 300°C at a heating rate of 5°C / min, and then heated to 1000°C at a heating rate of 2°C / min, the reaction time is 1h, and then the temperature is reduced to 300°C at a cooling rate of 7°C / min, and finally naturally cooled to room temperature to obtain a highly efficient, stable and multifunctional catalyst, during which no vapor deposition is carried out with sodium hypophosphite.
[0077] Comparative Example 4, a highly efficient, stable and multifunctional catalyst, is different from Example 1 only in that it is prepared according to the following steps: S1. Add 1.8 g of metal salt (the metal salt is ferric nitrate nonahydrate and cobalt acetate hexahydrate in a mass ratio of 2:1) to 100 ml of N,N-dimethylformamide and stir to dissolve, then add to 10 g of spinning precursor solution and continue to stir and disperse to obtain a spinning precursor solution containing metal ions, wherein the spinning precursor solution is polyacrylonitrile and the dihydroxy cage-type silsesquioxane prepared in Preparation Example 1 in a mass ratio of 1:0.1.
[0078] Then, composite fibers containing bimetallic nanoparticles are obtained by electrospinning. During the electrospinning process, a No. 19 needle is used, the spinning speed is 0.8 ml / h, the relative humidity of the air is controlled at 30%, the temperature is 25°C, and positive and negative voltages are loaded at the same time, wherein the positive voltage is 18 kv and the negative voltage is 0.1 kv.
[0079] S2. The composite fiber obtained in step S1 is vacuum dried at 120°C for 6 hours, and then heat treated under an ammonia gas flow, wherein the heat treatment heating rate is 2°C / min, heated to 800°C, and the heat treatment time is 2 hours, to obtain carbon fiber composite carbon nanotubes loaded with bimetallic nanoparticles, that is, a highly efficient, stable and multifunctional catalyst, without performing a vapor deposition step afterwards.
[0080] Performance testing 1. ORR performance test: The ORR performance test was carried out in an oxygen-saturated 0.1 M KOH solution, and the linear scanning polarity curves (LSV) of the embodiments and comparative examples were collected, wherein the LSV curves were collected at 1600 rpm and a scanning rate of 10 mV / s. The ORR performance was judged by the half-wave potential of the sample. The more positive the half-wave potential, the better the ORR activity.
[0081] 2. OER performance test: The OER performance test was carried out in a nitrogen-saturated 0.1 M KOH electrolyte, and the linear sweep polarity curves (LSV) of the embodiments and comparative examples were collected, where the constant current density was 10 mA / cm 2 The test scan rate is 5mV / s, and the OER performance is judged by the size of the obtained overpotential. The smaller the overpotential, the better the OER activity.
[0082] 3. Zinc-air battery test: The multifunctional catalyst obtained in the examples and comparative examples was applied to a zinc-air battery, and the catalytic activity of the catalyst was characterized by testing the discharge power density and cycle stability of the zinc-air battery. The zinc-air battery used 6.0M KOH and 0.2M Zn(OAc)2 aqueous solution as electrolyte and zinc sheet as anode.
[0083] The cycling stability of the assembled zinc-air battery was tested at 20 mA / cm 2 The charge and discharge cycle test under current density is 10 minutes per cycle. The stability of the charge and discharge cycles and the round-trip efficiency of the battery after 700 charge and discharge cycles are tested.
[0084] The test results of test 1 and test 2 are shown in Table 1, and the test results of test 3 are shown in Table 2.
[0085] Table 1 ORR / OER performance test results Table 2 Test results of zinc-air battery According to Table 1 and Table 2, in combination with Example 1, Example 2 to Example 9, it can be seen that the half-wave potential, overpotential, discharge power density, cycle stability number and energy round-trip efficiency of Example 2 to Example 9 are not significantly different from those of Example 1, indicating that the ORR / OER activity and stability of Example 2 to Example 9 are not significantly different from those of Example 1. The reason may be that the difference between Example 2 to Example 9 and Example 1 is only that the ratio of the raw materials added during the preparation of the catalyst is adjusted within the required range, indicating that changing the ratio of the raw materials within the required range has no significant effect on the performance and stability of the final catalyst.
[0086] Combining Example 1 and Example 10 to Example 12, it can be seen that the half-wave potential, overpotential, discharge power density, cycle stability number and energy round-trip efficiency of Example 10 to Example 12 are not significantly different from those of Example 1, indicating that the ORR / OER activity and stability of Example 10 to Example 12 are not significantly different from those of Example 1. The reason may be that the difference between Example 10 to Example 12 and Example 1 is only that the electrospinning and heat treatment process conditions are adjusted within the required range during the preparation of the catalyst, indicating that changing the corresponding process conditions within the required range has no significant effect on the performance and stability of the final catalyst.
[0087] Combining Example 1, Example 13 and Example 14, it can be seen that the half-wave potential, overpotential, discharge power density, cycle stability number and energy round-trip efficiency of Example 13 and Example 14 are not significantly different from those of Example 1, indicating that the ORR / OER activity and stability of Example 13 and Example 14 are not significantly different from those of Example 1. The reason may be that the difference between Example 13 and Example 14 compared with Example 1 is only that the raw materials of the dihydroxy cage silsesquioxane used in the spinning precursor solution are varied within the required range during the preparation process, indicating that the raw material ratio of the dihydroxy cage silsesquioxane is varied within the required range, which has little effect on the performance and stability of the catalyst finally obtained.
[0088] Combining Example 1, Example 15 and Example 16, it can be seen that the half-wave potential, overpotential, discharge power density, cycle stability number and energy round-trip efficiency of Example 15 and Example 16 are not significantly different from those of Example 1, indicating that the ORR / OER activity and stability of Example 15 and Example 16 are not significantly different from those of Example 1. The reason may be that the difference between Example 15 and Example 16 and Example 1 is only that different combinations of bimetallic nanoparticles are used, which has little effect on the catalytic performance and stability of the catalyst.
[0089] Combining Example 1, Example 17 and Example 18, it can be seen that the half-wave potential, discharge power density, cycle stability number and energy round-trip efficiency of Example 17 and Example 18 are reduced compared with Example 1, and the overpotential of Example 17 and Example 18 is increased compared with Example 1, wherein Example 17 decreases more significantly, indicating that the ORR / OER activity and stability of Example 17 and Example 18 are reduced compared with Example 1. The reason may be that Example 17 and Example 18 adjust the amount of metal salt added to the spinning precursor solution outside the required range, wherein the amount of metal salt added is reduced in Example 17, resulting in a decrease in the content of bimetallic nanoparticles loaded on the final catalyst, thereby resulting in a decrease in ORR / OER activity, and the amount of metal salt added is increased in Example 18, and the loading amount of its carbon-based carrier has reached saturation, and further addition will not significantly enhance the ORR / OER activity and stability of the catalyst, but will inhibit it.
[0090] In combination with Example 1, Example 19 and Example 20, it can be seen that the half-wave potential, discharge power density, cycle stability number and energy round-trip efficiency of Example 19 and Example 20 are reduced compared with Example 1, and the overpotential of Example 19 and Example 20 is increased compared with Example 1, indicating that the ORR / OER activity and stability of Example 19 and Example 20 are slightly reduced compared with Example 1. The reason may be that the difference between Example 19 and Example 20 compared with Example 1 is only that the amount of 2-mercaptoethanol added to the dihydroxy cage silsesquioxane used in the preparation process is changed outside the required range. Specifically, the amount of addition is reduced in Example 19, resulting in a decrease in the hydroxyl groups contained in the dihydroxy cage silsesquioxane, a decrease in the coordination effect with the metal ions, and a decrease in the enhancement effect on the catalyst activity. The amount of addition is increased in Example 20, resulting in an increase in the content of hydroxyl groups on the dihydroxy cage silsesquioxane. The coordination between too many hydroxyl groups and metal ions is not conducive to the subsequent formation of metal nitrides and metal phosphides, and the activity of the corresponding catalyst is reduced.
[0091] In combination with Example 1 and Example 21 to Example 23, it can be seen that the half-wave potential, discharge power density, cycle stability number and energy round-trip efficiency of Example 21 to Example 23 are reduced compared with Example 1, and the overpotential of Example 21 to Example 23 is increased compared with Example 1, among which Example 23 changes most significantly, indicating that the ORR / OER activity and stability of Example 21 to Example 23 are reduced compared with Example 1. The reason may be that the difference between Example 21 to Example 23 and Example 1 is that the addition amount of dihydroxy cage silsesquioxane in the spinning precursor solution changes outside the required range. Specifically, the addition amount of dihydroxy cage silsesquioxane in Example 21 is reduced, the content of hydroxyl active sites is reduced, the enhancement effect on the catalytic activity of the catalyst is reduced, the reduction of the porous structure also reduces the mass transfer in the system, and the rigid structure does lead to a slight decrease in stability. In Example 23, no dihydroxy cage silsesquioxane is added, and the performance decrease is more obvious. The increase in the amount of dihydroxy cage silsesquioxane added in Example 22 is also due to the increase in hydroxyl active sites, which is not conducive to the subsequent formation of metal nitrides and metal phosphides, and the activity of the corresponding catalyst decreases.
[0092] Combining Example 1 and Example 24 to Example 27, it can be seen that the half-wave potential, discharge power density, cycle stability number and energy round-trip efficiency of Example 24 to Example 27 are reduced compared with Example 1, and the overpotential of Example 24 to Example 27 is increased compared with Example 1, among which Example 24 and Example 26 have the most obvious changes, indicating that the ORR / OER activity and stability of Example 24 to Example 27 are reduced compared with Example 1. The reason may be that Example 24 to Example 27 changes the addition amount of nitrogen precursor and phosphorus precursor, among which Example 24 and Example 26 respectively reduce the addition amount of nitrogen precursor and phosphorus precursor, resulting in a decrease in the number of metal nitrides and metal phosphides formed, a decrease in ORR / OER activity, and a decrease in the catalytic activity of the corresponding catalyst.
[0093] Combining Example 1, Example 28 and Example 29, it can be seen that the half-wave potential, discharge power density, cycle stability number and energy round-trip efficiency of Example 28 and Example 29 are reduced compared with Example 1, and the overpotential of Example 28 and Example 29 is increased compared with Example 1, indicating that the ORR / OER activity and stability of Example 28 and Example 29 are reduced compared with Example 1. The reason may be that Example 28 and Example 29 replaced the needle model during the electrospinning process, wherein a needle with a larger diameter was used in Example 28, resulting in part of the spinning precursor solution being unable to form a spray during the ejection process, resulting in part of the product being unable to form a fiber, and finally resulting in the difficulty in forming a carbon fiber structure, the porosity and specific surface area being reduced, resulting in the catalyst activity and stability being reduced; a needle with a smaller diameter was used in Example 29, resulting in the spinning precursor solution being difficult to eject normally in a spray state, and the corresponding catalytic activity and stability being reduced.
[0094] Combining Example 1 and Comparative Example 1, it can be seen that the half-wave potential, discharge power density, cycle stability number and energy round-trip efficiency of Comparative Example 1 are lower than those of Example 1, and the overpotential of Comparative Example 1 is higher than that of Example 1, indicating that the ORR / OER activity and stability of Comparative Example 1 are lower than those of Example 1. The reason may be that a metal salt is used in Comparative Example 1, and the formed metal nanoparticles cannot form an alloy, and the alloy particles are more likely to form MOOH / MOH bonds on their surfaces than single metal nanoparticles, and the increase in the reaction activity of OER is more obvious, and a synergistic effect is formed between the two different metals, and the use of a single metal will lead to a more obvious decrease in the catalytic activity and stability of the obtained catalyst.
[0095] Combining Example 1 and Comparative Examples 2 to 4, it can be seen that the half-wave potential, discharge power density, cycle stability number and energy round-trip efficiency of Comparative Examples 2 to 4 are lower than those of Example 1, and the overpotential of Comparative Examples 2 to 4 is higher than that of Example 1, among which Comparative Example 4 has the most obvious change, indicating that the ORR / OER activity and stability of Comparative Examples 2 to 4 are lower than those of Example 1. The reason may be that no metal nitride or metal phosphide is formed in Comparative Examples 2 and 3, and the ORR / OER activity and stability of the catalyst are reduced due to the lack of one of the coordination compounds, while no coordination compound is formed in Comparative Example 4, and the content of ORR / OER active substances is reduced, resulting in a significant decrease in the ORR / OER activity and stability of the final catalyst.
[0096] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as it is within the scope of the claims of the present application, it shall be protected by the patent law.
Claims
1. A highly efficient, stable and multifunctional catalyst, characterized in that: The multifunctional catalyst is a carbon-based loaded bimetallic nanoparticle catalyst; the carbon-based catalyst is a carbon fiber composite carbon nanotube; the bimetallic nanoparticle is one of Fe-Co nanoparticles, Fe-Ni nanoparticles and Co-Ni nanoparticles; the carbon-based catalyst is also loaded with metal nitrides and metal phosphides.
2. The efficient, stable and multifunctional catalyst according to claim 1, characterized in that: The metal nitride is Fe-N x Coordination compounds, Co-N x Coordination compounds and Ni-N x At least one of the coordination compounds; the metal phosphide is Fe-P x Coordination compounds, Co-P x Coordination compounds and Ni-P x At least one of the coordination compounds.
3. The efficient, stable and multifunctional catalyst according to claim 1, characterized in that: The carbon fiber composite carbon nanotube contains nitrogen-doped graphene.
4. The efficient, stable and multifunctional catalyst according to claim 1, characterized in that: The carbon fiber composite carbon nanotube also contains dihydroxy cage-type silsesquioxane; the raw materials of the dihydroxy cage-type silsesquioxane include octavinyl cage-type silsesquioxane monomer and 2-mercaptoethanol in a mass ratio of 1: (0.35-0.4).
5. A method for preparing a highly efficient, stable and multifunctional catalyst according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: S1. adding a metal salt to a solvent, stirring and dissolving the metal salt, and then adding the metal salt to a spinning precursor solution, stirring and dispersing the solution to obtain a spinning precursor solution containing metal ions; and then electrospinning to obtain a composite fiber containing bimetallic nanoparticles; S2. The composite fiber obtained in step S1 is first dried and then heat treated under an ammonia gas flow to obtain a carbon fiber composite carbon nanotube loaded with bimetallic nanoparticles; S3. The obtained carbon fiber composite carbon nanotubes loaded with bimetallic nanoparticles and the nitrogen precursor are placed in the same crucible and vapor deposited in a nitrogen atmosphere; after the reaction is completed, the product and the phosphorus precursor are placed in two different crucibles and vapor deposited in a nitrogen atmosphere, and a highly efficient, stable and multifunctional catalyst is obtained after cooling.
6. The method for preparing a highly efficient, stable and multifunctional catalyst according to claim 5, characterized in that: In the step S1, a No. 19 needle is used for electrospinning, and the spinning speed is 0.5 to 1 ml / h; during the electrospinning process, positive and negative voltages need to be loaded simultaneously, the positive voltage is 15 to 20 kv, and the negative voltage is -0.2 to 0.8 kv.
7. The method for preparing a highly efficient, stable and multifunctional catalyst according to claim 5, characterized in that: In the step S2, the heat treatment temperature is 750-800° C. and the heat treatment time is 2-2.5 hours.
8. The method for preparing a highly efficient, stable and multifunctional catalyst according to claim 5, characterized in that: The metal salt comprises a combination of at least two of ferric nitrate nonahydrate, cobalt nitrate hexahydrate, cobalt acetate hexahydrate, ferrous sulfate heptahydrate, nickel nitrate hexahydrate, and nickel sulfate hexahydrate; the mass ratio of the metal salt to the spinning precursor solution is (0.15-0.2):
1.
9. The method for preparing a highly efficient, stable and multifunctional catalyst according to claim 5, characterized in that: The spinning precursor solution comprises a spinning polymer and dihydroxy cage-type silica in a mass ratio of 1: (0.05-0.15); the spinning polymer comprises one or a combination of polyacrylonitrile, polyaniline and polyvinyl pyrrolidone.
10. The method for preparing a highly efficient, stable and multifunctional catalyst according to claim 5, characterized in that: The nitrogen precursor includes one or a combination of dicyandiamide, urea, and melamine; the phosphorus precursor includes one or a combination of diammonium phosphate, sodium hypophosphite, and diammonium hydrogen phosphate; the mass ratio of the carbon fiber composite carbon nanotube loaded with bimetallic nanoparticles to the nitrogen precursor is 1: (3.5-4.5); the mass ratio of the carbon fiber composite carbon nanotube loaded with bimetallic nanoparticles to the phosphorus precursor is 1: (3-4).
Citation Information
Cited By
HER-OER bifunctional material as well as preparation and application thereof
CN120719311A